Pengaruh Pemahaman Perpajakan, Love of Money, dan Diskriminasi Perpajakan terhadap Persepsi Mahasiswa Mengenai Tax Evasion - Ryketeng, Masdar; Samsinar, Samsinar; Rahman, Ahmad Nashiruddin Mushoddiq (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to examine the influence of tax understanding, love of money, and tax discrimination on students' perceptions of tax evasion. The population in this study were students in the Applied Accounting Study Program at Makassar State University, while the sample was selected using a purposive sampling technique with the criteria of students who have acquired a basic understanding of taxation, namely Applied Accounting students from the 2021-2023 intake. Data were obtained through documentation methods and analyzed using the classical assumption test, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R2). The results showed that tax understanding, love of money, and tax discrimination simultaneously had a significant effect on students' perceptions of tax evasion. Partially, tax understanding and tax discrimination had a significant effect on tax evasion, while love of money had no significant effect. The coefficient of determination value of 23.6% indicates that the three independent variables are able to explain variations in tax evasion perceptions, while the remainder is influenced by other factors outside the model.